2021
DOI: 10.1088/1755-1315/896/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

The effect of land subsidence on the selection of raw water sources in hotel and apartment buildings in Semarang city

Abstract: The Semarang City Government prohibits groundwater/deep wells in hotel and apartment buildings because the use of groundwater or deep wells in locations that have experienced subsidence will further aggravate the subsidence. The method used in this research is to purposively select hotel and apartment buildings in Semarang that have received an assessment by the Semarang City Building Expert Team and have received a certificate of serviceability. Furthermore, compare the map of land subsidence in some areas of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The use in the type of bathing activity using a bathtub has an average water use of 413.37 liters/day, while using a bucket has an average water use of 349.58 liters/day. From the description above, it can be concluded that the use of water in the type of bathing activity using a bathtub tends to use more water compared to using a bucket [7].…”
Section: Domestic Water Usage By Type Of Activitymentioning
confidence: 99%
“…The use in the type of bathing activity using a bathtub has an average water use of 413.37 liters/day, while using a bucket has an average water use of 349.58 liters/day. From the description above, it can be concluded that the use of water in the type of bathing activity using a bathtub tends to use more water compared to using a bucket [7].…”
Section: Domestic Water Usage By Type Of Activitymentioning
confidence: 99%
“…To carry out rainwater harvesting, several variables are needed, such as local rainfall data, roof area, type of water catchment surface, rainwater needs, and drinking water needs [5]. The application of RWH for sustainable water management entails numerous factors, including decentralization of public water delivery systems and flood prevention [6]. RWH is one method for diversifying water sources and increasing water security [7].…”
Section: Introductionmentioning
confidence: 99%
“…RWH is one method for diversifying water sources and increasing water security [7]. RWH has the potential to lessen the environmental effects of buildings and cities, making them more sustainable [8].…”
Section: Introductionmentioning
confidence: 99%
“…The number of rainy days tends to decrease, but the maximum daily rainfall and its intensity tend to increase [2]. Covering the land surface further increases surface water runoff and reduces the entry of water into the ground [3].…”
Section: Introductionmentioning
confidence: 99%
“…Water drainage systems in buildings in the city of Semarang, especially in apartment and hotel buildings, often make mistakes in their design. The mistake that often occurs is not distinguishing which is an appropriate location for infiltration wells and disposal into urban drainage, often apartment and hotel buildings do not pay attention to soil permeability and depth of groundwater in their disposal system [8].…”
Section: Introductionmentioning
confidence: 99%